2015
DOI: 10.9798/kosham.2015.15.6.321
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Unsaturated Soil Slope Considering Rainfall Infiltration by Two-Pahse Flow Model

Abstract: 서 론우리나라는 AbstractMost previous studies on the rainfall infiltration and its influence on slope stability were based on the single-phase water flow model. The purpose of this study is to study the effect of interaction of air and water flow on the slope stability. In this study, two-phase flow analyses were conducted for weathered residual soil slopes with thin soil overlying impermeable bedrock. Results of the flow analysis were used as input for stability analysis by strength reduction method. Strength reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As such, the test methods for measuring the permeability coefficient and shear strength were more complicated than the test for the basic physical properties of soil and required expert skills. However, permeability coefficients and shear strength constants of various points were required to understand the soil characteristics and identify the failure mechanism in the landslide areas [42,43]. Thus, a considerable amount of time and costs were necessary to obtain the results.…”
Section: Estimation Of Landslide-triggering Factors Using Soil Proper...mentioning
confidence: 99%
“…As such, the test methods for measuring the permeability coefficient and shear strength were more complicated than the test for the basic physical properties of soil and required expert skills. However, permeability coefficients and shear strength constants of various points were required to understand the soil characteristics and identify the failure mechanism in the landslide areas [42,43]. Thus, a considerable amount of time and costs were necessary to obtain the results.…”
Section: Estimation Of Landslide-triggering Factors Using Soil Proper...mentioning
confidence: 99%
“…Terzaghi (1950) first presented that rainfall-induced landslides are caused by increased pore pressures and seepage forces during periods of intense rainfall. Cho (2015) found that the infiltration of rainwater will significantly reduce the matric suction of unsaturated soil and the anti-slide force, thus causing slope failures. Matsuura and Wang proposed that most shallow landslides are induced by the change of transient pore water pressure due to short-term concentrated rainfalls (Matsuura 20088;Wang and Sassa 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although slope failures may develop due to many factors, such as earthquakes, human-induced factors including the loading of the slope or excavation for construction purposes, the occurrence of landslides in residual soils is mainly attributed to rainfall (Brand 1981(Brand , 1984Fredlund and Rahardjo 1994;Lim et al 1996;Rahardjo et al 1996;Tsukamoto 1998;Montrasio and Valentino et al 2009;Cho 2015). Furthermore, most of the rainfall-induced landslides in residual soils consist of relatively shallow slips above the groundwater table with the thickness of sliding mass smaller than 5 m approximately, and slide along the interface between the soil layer and underlying bedrock Montrasio and Valentino 2009).…”
Section: Introductionmentioning
confidence: 99%